Developing an occupational science curriculum for undergraduate students. - Payne, Kristy; Crowley, Kate (Journal of Occupational Science, 2021)
Developing an occupational science curriculum that is responsive to the specific needs of a student population manifests Dr. Elizabeth Yerxa's (1990) vision of leveraging the ideas of occupational science to meet the complex social challenges of our time. Through a case example of the Occupational Science Minor Program at the University of Southern California (USC), we demonstrate that the translation of occupational science as a basic science can be interpreted in a meaningful way to undergraduate students in light of the current mental health needs of this population. Dr. Ruth Zemke (2016) traced the creation of the USC Occupational Science Minor Program as a way to extend occupational science education and advance the field to the next generation of researchers, clinicians, and stakeholders. In this paper, the authors expand upon Zemke's introduction of the program and explore the guiding principles for developing an occupational science curriculum for undergraduate students. We draw from current research in occupational therapy and occupational science education as well as evidenced-based curricula design strategies from education in order to identify program strengths and opportunities for improvement.